Heritage science : expanding the thinkable future beyond inherited pasts and the visible presents - Nanetti, Andrea (2020)
The Ginkgo Meeting perfectly works as a show case to demonstrate how a basic tool of research methods is needed to set an effective stage for interdisciplinary approaches to complex ideas. The proceedings of the meeting that are published in this book present a collection of interpretations, whose appreciation would highly benefit from a clear understanding of both the common definition, from which they all start, and the different assumptions, on which each author's discipline bases its own different discourse.